The Implication of Land Acquisition for the Supply Chain development Management of National Strategic Project towards Sustainable Agricultural/Farming Land: the Case Study of the development Project of Jakarta-Bandung Rapid Train - Yani Pujiwati; Supraba Sekarwati; Maret Priyanta; Yulinda Adharani; Siti Sarah Afifah (International Journal of Supply Chain Management, 2020)
Indonesia is in the middle of increasing the land acquisition made for the public interest, since the focus of the Indonesian government currently is to develop the infrastructure necessary for the public. The case considered in this paper is the construction in the infrastructure of Jakarta-Bandung Rapid Train. In the execution of supply chain development of the Jakarta-Bandung Rapid Train, the government is using the acquisition of land from the public, of which, agricultural land along the train-route must be handed-over for the sake of the supply chain development. This is interesting to study because there has been a change of function of agricultural land to non-agricultural land, in the Article 44 paragraph (1) of the Law Number 41 of 2009 concerning the Protection of Sustainable agricultural/farming land, it is stated that land that has been designated as sustainable agricultural/farming land is under protection and its acquisition, should not be conversed for other purpose. However, in the paragraph (2), it is stated that with respect to the public interest, the sustainable agricultural/farming land, might have conversion to purpose according to the rules and regulations. This study is using a normative juridical approach and it has analytical descriptive nature. It describes theories about the land acquisition, sustainable agricultural/farming land, and other related theories. The result shows that the supply chain development of the Jakarta-Bandung Rapid Train project executed was apparently not in accordance with the Spatial Zoning Plan (SZP) of the area where the supply chain development is taking place, meanwhile, the Law Number 2 concerning the Land Acquisition for Supply chain development in the Public Interest requires the supply chain development to be in line with the SZP, for that matter, the government is initiating solution on changing the SZP.